High-frequency rTMS modulates emotional behaviors and structural plasticity in layers II/III and V of the mPFC - Cambiaghi, Marco; Infortuna, Carmenrita; Gualano, Francesca; Elsamadisi, Amir; Malik, Wasib; Buffelli, Mario; Han, Zhiyong; Solhkhah, Ramon; P. Thomas, Florian; Battaglia, Fortunato (Frontiers in Cellular Neuroscience, 2022)
Repetitive Transcranial magnetic stimulation (rTMS) is a noninvasive neuromodulation technique, and it has been increasingly used as a nonpharmacological intervention for the treatment of various neurological and neuropsychiatric diseases, including depression. In humans, rTMS over the prefrontal cortex is used to induce modulation of the neural circuitry that regulates emotions, cognition, and depressive symptoms. However, the underlying mechanisms are still unknown. In this study, we investigated the effects of a short (5-day) treatment with high-frequency (HF) rTMS (15 Hz) on emotional behavior and prefrontal cortex morphological plasticity in mice. Mice that had undergone HF-rTMS showed an anti-depressant-like activity as evidenced by decreased immobility time in both the Tail Suspension Test and the Forced Swim Test along with increased spine density in both layer II/III and layer V apical and basal dendrites. Furthermore, dendritic complexity assessed by Sholl analysis revealed increased arborization in the apical portions of both layers, but no modifications in the basal dendrites branching. Overall, these results indicate that the antidepressant-like activity of HF-rTMS is paralleled by structural remodeling in the medial prefrontal cortex.